Quantitative Analysis of Lithium in Natural Brines from the Lithium Triangle by Laser-Induced Breakdown Spectroscopy - Juan Molina M.; Carisa Sarchi; Alvaro Y. Tesio; César Costa-Vera; Diego M. Díaz Pace (Atoms, 2025)
Lithium (Li)-rich continental brines found in the Lithium Triangle region in South America are a natural resource of paramount importance. In the present research, the analytical performance of laser-induced breakdown spectroscopy (LIBS) technology was assessed for the quantitative analysis of Li in natural brines aimed at enhancing the efficient exploration of salt flats (called salars). Brine samples were collected from different salars located in the Puna plateau (Northwest Argentina) and analyzed by LIBS in the form of solid pressed pellets. Broadband emission spectra (180–900 nm) were recorded and spectrally analyzed by specially designed computational algorithms. The laser-induced plasmas were characterized by calculating the electron density and the temperature. The Li elemental concentrations in the brines were determined through univariate calibration with the Li I emission line at 670.77 nm by using a suitable set of standards with Li concentrations up to 1300 <semantics>μ</semantics>g/g. The calculated limit of detection was LoD = 0.2 ± 0.1 <semantics>μ</semantics>g/g. The Li content in the brines determined with LIBS showed a good agreement (normalized standard deviation: σN = 25%) with the concentrations measured with atomic absorption spectroscopy. The results demonstrated the feasibility of the LIBS technique for the quantitative analysis of Li in natural brines, thus contributing to advancing the exploration of Li-rich resources.